2002
DOI: 10.1161/01.cir.0000024102.55150.b6
|View full text |Cite
|
Sign up to set email alerts
|

Postsystolic Shortening in Ischemic Myocardium

Abstract: Background-Postsystolic shortening in ischemic myocardium has been proposed as a marker of tissue viability. Our objectives were to determine if postsystolic shortening represents active fiber shortening or passive recoil and if postsystolic shortening may be quantified by strain Doppler echocardiography (SDE). Methods and Results-In 15 anesthetized dogs, we measured left ventricular (LV) pressure, myocardial long-axis strains by SDE, and segment lengths by sonomicrometry before and during LAD stenosis and occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(161 citation statements)
references
References 24 publications
11
145
0
5
Order By: Relevance
“…pulmonary valve) [51]. It is a well described phenomenon in both ischemic-and non-ischemic cardiomyopathies [51][52][53]. The exact mechanism of PSS is unclear.…”
Section: Deformation After Pulmonary Valve Closurementioning
confidence: 99%
“…pulmonary valve) [51]. It is a well described phenomenon in both ischemic-and non-ischemic cardiomyopathies [51][52][53]. The exact mechanism of PSS is unclear.…”
Section: Deformation After Pulmonary Valve Closurementioning
confidence: 99%
“…The mechanisms of postsystolic shortening were investigated by Skulstad et al (9), and it was found that postsystolic shortening was a relatively nonspecific feature of the ischemic myocardium. It could occur in severely ischemic myocardium by an entirely passive process, then representing passive recoil of dyskinetic segments.…”
Section: Apical Flow Reversal: Diagnostic Implicationsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] It is frequently observed in patients with CAD presenting with LV asynergy. [23][24][25] Earlier studies have demonstrated the presence of abnormal diastolic function in patients with CAD without evidence of systolic wall motion abnormalities by radionuclide angiography or digitized cineangiography.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical [3][4][5] and animal studies [6][7][8][9][10] have demonstrated that PSS is related to myocardial ischemia.…”
Section: Editorial P 37mentioning
confidence: 99%
See 1 more Smart Citation